Hot melt adhesive sheet
The hot melt adhesive sheet with a specific crosslinked adhesive composition addresses the issue of edge embedding and thickness uniformity in polymer electrolyte fuel cells, improving efficiency by using a bisphenol-type epoxy resin with controlled crosslinking density.
Patent Information
- Application Number
- JP2023110117
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2043-07-04
AI Technical Summary
Existing hot melt adhesive sheets fail to sufficiently embed the outer edges of solid electrolyte membranes in polymer electrolyte fuel cells, leading to uneven thickness and reduced power generation efficiency.
A hot melt adhesive sheet with a crosslinked adhesive composition containing a polyester resin, bisphenol-type epoxy resin, and isocyanate crosslinking agent, where the bisphenol-type epoxy resin has an epoxy equivalent of 450 g/eq to 1000 g/eq, ensuring appropriate crosslinking density and mechanical strength, is used to adhere to the solid electrolyte membrane, embedding the edges and preventing uneven thickness.
The adhesive sheet effectively embeds the outer edges of the solid electrolyte membrane, maintaining uniform thickness and enhancing power generation efficiency in polymer electrolyte fuel cells, even under high temperature and acidic conditions.
Smart Images

Figure 2025008174000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot melt adhesive sheet. [Background technology]
[0002] 2. Description of the Related Art Hot melt adhesive sheets having an adhesive layer formed from a hot melt adhesive are conventionally known. It is also known to use such a hot melt adhesive sheet by adhering it to a solid electrolyte membrane of a polymer electrolyte fuel cell (for example, Patent Document 1 below).
[0003] As described in Patent Document 1 below, the solid polymer fuel cell typically includes a membrane electrode assembly (MEA), which is configured such that a positive electrode and a negative electrode are disposed on each of the opposing sides of a solid electrolyte membrane. Here, in the solid polymer fuel cell, the positive electrode is usually configured so that a positive electrode gas diffusion layer is disposed on a positive electrode catalyst layer, and the negative electrode is usually configured so that a negative electrode gas diffusion layer is disposed on a negative electrode catalyst layer. In the membrane electrode assembly (MEA), the positive electrode catalyst layer of the positive electrode is disposed on one side of the solid electrolyte membrane, and the negative electrode catalyst layer of the negative electrode is disposed on the other side of the solid electrolyte membrane.
[0004] In addition, the positive electrode catalyst layer and the negative electrode catalyst layer are configured to have planar dimensions smaller than the solid electrolyte membrane, the positive electrode gas diffusion layer is configured to have planar dimensions smaller than the positive electrode catalyst layer, and the negative electrode gas diffusion layer is configured to have planar dimensions smaller than the negative electrode catalyst layer.
[0005] Therefore, when the membrane electrode assembly (MEA) is viewed in plan from one side, the outer edge of the solid electrolyte membrane on one side extends outward beyond the outer edge of the positive electrode catalyst layer of the positive electrode, and when the membrane electrode assembly (MEA) is viewed in plan from the other side, the outer edge of the solid electrolyte membrane on the other side extends outward beyond the outer edge of the negative electrode catalyst layer of the negative electrode. That is, when the membrane electrode assembly (MEA) is viewed in plan from one side, one exposed surface is formed on the outer edge side of one side of the solid electrolyte membrane between the outer edge of the one side of the solid electrolyte membrane and the outer edge of the positive electrode catalyst layer, and when the membrane electrode assembly (MEA) is viewed in plan from the other side, another exposed surface is formed on the outer edge side of the other side of the solid electrolyte membrane between the outer edge of the other side of the solid electrolyte membrane and the outer edge of the negative electrode catalyst layer.
[0006] As described in Patent Document 1 below, the hot melt adhesive sheet is adhered to the solid electrolyte membrane by sandwiching the one exposed surface of the solid electrolyte membrane and the other exposed surface of the solid electrolyte membrane between two hot melt adhesive sheets. More specifically, an adhesive layer of one of the hot melt adhesive sheets is adhered to the one exposed surface of the solid electrolyte membrane, and an adhesive layer of the other of the hot melt adhesive sheets is adhered to the other exposed surface of the solid electrolyte membrane. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2019 / 216402 Summary of the Invention [Problem to be solved by the invention]
[0008] However, as described above, after adhering the adhesive layer of one of the hot melt adhesive sheets to one exposed surface of the solid electrolyte membrane and adhering the adhesive layer of the other hot melt adhesive sheet to the other exposed surface of the solid electrolyte membrane, a large gap may be generated between the outer edge of the solid electrolyte membrane and the adhesive layer. In other words, the outer edge of the solid electrolyte membrane may not be fully embedded by the adhesive layer of the hot melt adhesive sheet.
[0009] In addition, after adhering an adhesive layer of one of the hot melt adhesive sheets to one exposed surface of the solid electrolyte membrane and adhering an adhesive layer of the other of the hot melt adhesive sheets to the other exposed surface of the solid electrolyte membrane, the thickness of the adhesive layer may become non-uniform.
[0010] As described above, it is undesirable that the outer edge of the solid electrolyte membrane cannot be sufficiently embedded by the adhesive layer of the hot melt adhesive sheet, and that the thickness of the adhesive layer of the hot melt adhesive sheet becomes uneven, as this leads to a decrease in the power generation efficiency of the solid polymer fuel cell. However, it cannot be said that sufficient consideration has yet been given to solving both the problems of sufficiently embedding the outer edges of the solid electrolyte membrane with the adhesive layer of the hot melt adhesive sheet and preventing the thickness of the adhesive layer of the hot melt adhesive sheet from becoming uneven.
[0011] The present invention has been made to solve the above problems, and has an object to provide a hot melt adhesive sheet that can sufficiently embed the outer edges of the solid electrolyte membrane with the adhesive layer after the adhesive layer is adhered to the solid electrolyte membrane of a solid polymer fuel cell, and can also suppress unevenness in the thickness of the adhesive layer. [Means for solving the problem]
[0012] The hot melt adhesive sheet according to the present invention is A hot melt adhesive sheet having an adhesive layer formed of a hot melt adhesive laminated on at least one surface of a substrate, The hot melt adhesive includes a crosslinked product of an adhesive composition including a crosslinking agent, the adhesive composition including a polyester resin, an epoxy resin, and an isocyanate-based crosslinking agent; The epoxy resin includes a bisphenol type epoxy resin and a rubber-modified epoxy resin, The bisphenol type epoxy resin has an epoxy equivalent of 450 g / eq or more and 1000 g / eq or less. Effect of the Invention
[0013] According to the present invention, it is possible to provide a hot melt adhesive sheet which, after adhering an adhesive layer to a solid electrolyte membrane of a solid polymer fuel cell, can achieve both of the following: the outer edge of the solid electrolyte membrane is sufficiently embedded by the adhesive layer, and the thickness of the adhesive layer is prevented from becoming uneven. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic cross-sectional view showing a configuration of a hot melt adhesive sheet according to one embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing a state in which a hot melt adhesive sheet according to an embodiment of the present invention is attached to a solid electrolyte membrane of a polymer electrolyte fuel cell and used; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, a hot melt adhesive sheet according to one embodiment of the present invention will be described with reference to the drawings. Hereinafter, one embodiment of the present invention may be simply referred to as the present embodiment.
[0016] As shown in FIG. 1, a hot melt adhesive sheet 10 according to this embodiment is a hot melt adhesive sheet in which an adhesive layer 10b formed of a hot melt adhesive is laminated on one surface of a substrate 10a. In the hot melt adhesive sheet 10 shown in FIG. 1, the adhesive layer 10b is laminated only on one surface of the substrate 10a, but the adhesive layer 10b may be laminated on the other surface of the substrate 10a. That is, the hot melt adhesive sheet 10 may be a hot melt adhesive sheet in which adhesive layers 10b are laminated on both sides of a substrate 10a.
[0017] In the hot melt adhesive sheet 10 according to this embodiment, the hot melt adhesive comprises a crosslinked product of an adhesive composition containing a crosslinking agent. In the hot melt adhesive sheet 10 according to this embodiment, the adhesive composition contains a polyester resin, an epoxy resin, and an isocyanate-based crosslinking agent. In the hot melt adhesive sheet 10 according to this embodiment, the epoxy resin includes a bisphenol type epoxy resin and a rubber-modified epoxy resin. In the hot melt adhesive sheet 10 according to this embodiment, the bisphenol type epoxy resin has an epoxy equivalent of 450 g / eq or more and 1000 g / eq or less.
[0018] Hereinafter, the polyester resin will be referred to as polyester resin (A), the epoxy resin will be referred to as epoxy resin (B), and the isocyanate-based crosslinking agent will be referred to as isocyanate-based crosslinking agent (C). Among the polyester resins (A), the crystalline polyester resin is referred to as a crystalline polyester resin (a1), and the non-crystalline polyester resin is referred to as a non-crystalline polyester resin (a2). Furthermore, among the epoxy resins (B), the bisphenol type epoxy resins are referred to as bisphenol type epoxy resins (b1), and the rubber-modified epoxy resins are referred to as rubber-modified epoxy resins (b2).
[0019] The hot melt adhesive sheet 10 according to this embodiment is used by adhering it to a solid electrolyte membrane 201 of a polymer electrolyte fuel cell, for example, as described below. A solid polymer fuel cell typically comprises a membrane electrode assembly (MEA) 20, which is configured such that a positive electrode 202 and a negative electrode 203 are disposed on either side of a solid electrolyte membrane 201, the sides of which face each other. In the membrane electrode assembly (MEA) 20, the positive electrode 202 is configured such that a positive electrode gas diffusion layer 202b is arranged on a positive electrode catalyst layer 202a, and the negative electrode 203 is configured such that a negative electrode gas diffusion layer 203b is arranged on a negative electrode catalyst layer 203a. That is, in the membrane electrode assembly (MEA) 20, a positive electrode catalyst layer 202a and a positive electrode gas diffusion layer 202b are arranged in this order on one side of a solid electrolyte membrane 201 to form a positive electrode 202, and a negative electrode catalyst layer 203a and a negative electrode gas diffusion layer 203b are arranged in this order on the other side of the solid electrolyte membrane 201 to form a negative electrode 203.
[0020] When the membrane electrode assembly (MEA) 20 is viewed in a plan view from one side, the outer edge of the one side of the solid electrolyte membrane 201 extends outward beyond the outer edge of the positive electrode catalyst layer 202a, and the outer edge of the positive electrode catalyst layer 202a extends outward beyond the outer edge of the positive electrode gas diffusion layer 202b. In addition, when the membrane electrode assembly (MEA) 20 is viewed in plan from the other side, the outer edge of the solid electrolyte membrane 201 on the other side extends outward beyond the outer edge of the negative electrode catalyst layer 203a, and the outer edge of the negative electrode catalyst layer 203a extends outward beyond the outer edge of the negative electrode gas diffusion layer 203b. That is, on the outer edge side of one side of the solid electrolyte membrane 201, a first exposed surface (a cathode-side electrolyte membrane exposed region 201a described later) is formed between the outer edge of the one side of the solid electrolyte membrane 201 and the outer edge of the positive electrode catalyst layer 202a, and on the outer edge side of the positive electrode catalyst layer 202a, a second exposed surface (a cathode-side catalyst layer exposed region 202a1 described later) is formed between the outer edge of the positive electrode catalyst layer 202a and the positive electrode gas diffusion layer 202b. In addition, on the outer edge side of the other side of the solid electrolyte membrane 201, a third exposed surface (anode-side electrolyte membrane exposed region 201b described later) is formed between the outer edge of the other side of the solid electrolyte membrane 201 and the outer edge of the anode catalyst layer 203a, and a fourth exposed surface (anode-side catalyst layer exposed region 203a1 described later) is formed between the outer edge of the anode catalyst layer 203a and the anode gas diffusion layer 203b.
[0021] In the membrane / electrode assembly (MEA) 20 configured as described above, the hot melt adhesive sheet 10 is adhered to the solid electrolyte membrane 201 by sandwiching the solid electrolyte membrane 201 from both sides (i.e., one side and the other side) using two hot melt adhesive sheets 10. The two hot melt adhesive sheets 10 are used to sandwich the solid electrolyte membrane 201 from both sides thereof in such a manner that the adhesive layer 10b of one hot melt adhesive sheet 10 is adhered to the first exposed surface formed on one side of the solid electrolyte membrane 201 and the second exposed surface formed on the positive electrode catalyst layer 202a, and the adhesive layer 10b of the other hot melt adhesive sheet 10 is adhered to the third exposed surface formed on the other side of the solid electrolyte membrane 201 and the fourth exposed surface formed on the negative electrode catalyst layer 203a.
[0022] Here, the epoxy equivalent (unit: g / eq) means the molecular weight of the epoxy resin per functional group (glycidyl group). Therefore, it can be said that the smaller the epoxy equivalent value, the greater the number of epoxy groups per structural unit in the epoxy resin, and the greater the epoxy equivalent value, the fewer the number of epoxy groups per structural unit in the epoxy resin. Therefore, the smaller the epoxy equivalent value of an epoxy resin used, the higher the crosslink density with which the epoxy resin is cured. In other words, an epoxy resin with a small epoxy equivalent value becomes a cured product with a high crosslink density by being crosslinked. On the other hand, the higher the epoxy equivalent value of an epoxy resin used, the lower the crosslink density at which the epoxy resin is cured. That is, an epoxy resin with a high epoxy equivalent value is crosslinked to form a cured product with a low crosslink density. A hardened body having a high crosslink density exhibits high mechanical strength, but has poor ductility in proportion to the high mechanical strength, while a hardened body having a low crosslink density exhibits high ductility, but has poor mechanical strength in proportion to the high ductility.
[0023] Here, in the hot melt adhesive sheet 10 according to this embodiment, the hot melt adhesive for forming the adhesive layer 10b contains a bisphenol-type epoxy resin having an appropriate epoxy equivalent of 450 g / eq or more and 1000 g / eq, so that when the adhesive layer 10b is heated for use, the bisphenol-type epoxy resin can be crosslinked in the adhesive layer 10b at an appropriate crosslinking density. Therefore, the adhesive layer 10b of the hot melt adhesive sheet 10 according to this embodiment can exhibit a good balance of appropriate mechanical strength and appropriate ductility when used after heating. That is, the adhesive layer 10b of the hot melt adhesive sheet 10 according to this embodiment can exhibit suitable toughness when used after being heated. The hot melt adhesive contains the polyester resin in addition to the bisphenol type epoxy resin. The polyester resin has a characteristic of having a high elastic modulus, and due to the high elastic modulus, has a characteristic of having excellent restoring properties. Therefore, when the adhesive layer 10b formed by the hot melt adhesive is heated and used, it can exhibit the resilience due to the polyester resin in addition to the toughness due to the bisphenol type epoxy resin. Furthermore, since the hot melt adhesive contains a rubber-modified epoxy resin as the epoxy resin, the adhesive layer 10b formed by the hot melt adhesive can exhibit appropriate rubber elasticity when heated and used. Since the adhesive layer 10b of the hot melt adhesive sheet 10 in this embodiment exhibits the various properties as described above, when the adhesive layer 10b of one hot melt adhesive sheet 10 is adhered to the first exposed surface of the solid electrolyte membrane 201 and the adhesive layer 10b of the other hot melt adhesive sheet 10 is adhered to the third exposed surface of the solid electrolyte membrane 201, as described above, it is possible to sufficiently prevent gaps from being generated between the adhesive layer 10b of one hot melt adhesive sheet 10 and the outer edge of the solid electrolyte membrane 201, and between the adhesive layer 10b of the other hot melt adhesive sheet 10 and the outer edge of the solid electrolyte membrane 201. That is, the outer edge of the solid electrolyte membrane 201 can be sufficiently embedded by the adhesive layer 10b of one hot melt adhesive sheet 10 and the adhesive layer 10b of the other hot melt adhesive sheet 10. Furthermore, since the adhesive layer 10b of the hot melt adhesive sheet 10 has the above-mentioned properties, particularly the resilience and rubber elasticity, when the adhesive layer 10b of one hot melt adhesive sheet 10 is adhered to the first exposed surface of the solid electrolyte membrane 201 and the adhesive layer 10b of the other hot melt adhesive sheet 10 is adhered to the third exposed surface of the solid electrolyte membrane 201, it is possible to prevent the thickness of the adhesive layer 10b of one hot melt adhesive sheet 10 and the thickness of the adhesive layer 10b of the other hot melt adhesive sheet 10 from becoming uneven.
[0024] (Polyester resin (A)) As the polyester resin (A), a resin obtained by dehydration condensation of a polyvalent carboxylic acid and a polyol can be used. As the polyester resin (A), various known resins can be used. The polyester resin (A) may be an unmodified polyester resin or a modified polyester resin. The unmodified polyester resin means a polyester resin whose structure is not partially modified by a modifying component, and the modified polyester resin means a polyurethane resin whose structure is partially modified by a modifying component.
[0025] The modified polyester resin may be a urethane-modified polyester resin in which a part of the structure is modified by an isocyanate component as a modifying component, or a silicone-modified polyester resin in which a part of the structure is modified by a silicone component as a modifying component.
[0026] The urethane-modified polyester resin can be obtained, for example, by subjecting the polyvalent carboxylic acid and the polyol to dehydration condensation to obtain a polyester resin, and then reacting a terminal hydroxyl group of the polyester resin with an isocyanate component. The urethane-modified polyester resin can also be obtained by simultaneously reacting the polyvalent carboxylic acid, the polyol, and the isocyanate component. Examples of commercially available urethane-modified polyester resins include "Vylon (registered trademark) UR-3210" manufactured by Toyobo Corporation and "Vylon (registered trademark) UR-4410" manufactured by Toyobo Corporation.
[0027] The silicone-modified polyester resin can be obtained, for example, by reacting the polyvalent carboxylic acid, the polyol, and a modified silicone component having a reactive functional group at one or both ends. Examples of the reactive functional group contained in the modified silicone component include a hydroxy group, a carboxy group, and an epoxy group.
[0028] The polyester resin (A) may be a crystalline polyester resin (a1) or a non-crystalline polyester resin (a2). That is, the unmodified polyester resin and the modified polyester resin may be either a crystalline polyester resin (a1) or a non-crystalline polyester resin (a2).
[0029] The crystalline polyester resin (a1) refers to a polyester resin, among the unmodified polyester resin and the modified polyester resin, that exhibits at least one of a peak due to crystallization and a peak due to crystal melting when measured using a differential scanning calorimeter (DSC). The non-crystalline polyester resin (a2) refers to a polyester resin, among the unmodified polyester resin and the modified polyurethane resin, which does not show any peak due to crystallization or any peak due to crystalline melting in the measurement using the differential scanning calorimeter (DSC).
[0030] Therefore, when it is necessary to determine whether the polyester resin (A) is a crystalline polyester resin (a1) or a non-crystalline polyester resin (a2), the determination can be made by measuring using DSC and checking whether at least one of a peak due to crystallization and a peak due to crystal melting is confirmed.
[0031] Commercially available products of the crystalline polyester resin (a1) include products under the trade names "GM920" (manufactured by Toyobo Corporation), "GM913" (manufactured by Toyobo Corporation), "GM-350" (manufactured by Toyobo Corporation), "GM-900" (manufactured by Toyobo Corporation), "UE-9400" (manufactured by Unitika Ltd.), "UE-3400" (manufactured by Unitika Ltd.), and "UE-3410" (manufactured by Unitika Ltd.).
[0032] In addition, in the adhesive layer 10b of the hot melt adhesive sheet 10, if a portion of the epoxy resin (B) is in an unopened state (unreacted state), when the polyester resin (A) is hydrolyzed to a short chain having a hydroxyl group or a carboxyl group at the molecular end, the unreacted epoxy groups can be reacted with these to make the polyester resin (A) longer-chain again.
[0033] Examples of the polyvalent carboxylic acid constituting the polyester resin (A) include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, and biphenyldicarboxylic acid; aromatic oxycarboxylic acids such as p-oxybenzoic acid and p-(hydroxyethoxy)benzoic acid; saturated aliphatic dicarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid; unsaturated aliphatic dicarboxylic acids such as fumaric acid, maleic acid, and itaconic acid; unsaturated alicyclic dicarboxylic acids such as tetrahydrophthalic acid; alicyclic dicarboxylic acids such as hexahydrophthalic acid and 1,2-cyclohexanedicarboxylic acid; and tricarboxylic acids and tetracarboxylic acids such as trimellitic acid, trimesic acid, and pyromellitic acid.
[0034] Examples of the polyol constituting the polyester resin (A) include aliphatic glycols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, and 2-butyl-2-ethyl-1,3-propanediol; oligoalkylene glycols such as diethylene glycol, triethylene glycol, and dipropylene glycol; alicyclic glycols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol; polyalkylene ether glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; triols such as trimethylolethane, trimethylolpropane, glycerin, and pentaerythritol; ethylene oxide adducts and propylene oxide adducts of bisphenol A, and ethylene oxide adducts and propylene oxide adducts of hydrogenated bisphenol A.
[0035] The polyester resin (A) preferably contains a crystalline polyester resin (a1) having a softening point of 120° C. or higher. The softening point of the crystalline polyester resin (a1) is the softening point determined by the ring and ball method of JIS K 7234. In the hot melt adhesive sheet 10 according to this embodiment, the adhesive layer 10b contains the crystalline polyester resin (a1) having the softening point as described above, and therefore the adhesive layer 10b can be further prevented from softening in a high temperature (e.g., 95°C) environment. As a result, after adhesive layer 10b is bonded to the first exposed surface and the third exposed surface of solid electrolyte membrane 201, the adhesive layer 10b can sufficiently embed the outer edge of solid electrolyte membrane 201 and can prevent the thickness from becoming uneven. In addition, the adhesive layer 10b has excellent hot water resistance, acid resistance, and alcohol resistance. For example, when the adhesive layer 10b of the hot melt adhesive sheet 10 according to this embodiment is used by being adhered to the solid electrolyte membrane of a polymer electrolyte fuel cell, the adhesive layer 10b can sufficiently maintain adhesion to the solid electrolyte membrane 201 even when it comes into contact with water contained in antifreeze and alcohols such as polyethylene glycol at high temperatures such as 95°C, or is exposed to highly acidic conditions. An example of a commercially available crystalline polyester resin (a1) having a softening point of 120° C. or higher is "GM-913" manufactured by Toyobo Corporation.
[0036] The softening point of the crystalline polyester resin (a1) may be 140° C. or lower, 135° C. or lower, or 130° C. or lower.
[0037] The crystalline polyester resin (a1) preferably has a glass transition temperature Tg of -65°C or lower. By having the above-mentioned glass transition temperature Tg, the crystalline polyester resin (a1) can exhibit a sufficient rubbery state in a high-temperature (for example, 95° C.) environment. Therefore, in the hot melt adhesive sheet 10 according to this embodiment, since the adhesive layer 10b contains the crystalline polyester resin (a1) having the above-mentioned glass transition temperature Tg, the adhesive layer 10b can also exhibit a sufficient rubbery state even in a high temperature environment. As a result, after adhesive layer 10b is bonded to the first exposed surface and the third exposed surface of solid electrolyte membrane 201, the adhesive layer 10b can sufficiently embed the outer edge of solid electrolyte membrane 201 and can prevent the thickness from becoming uneven. In addition, the adhesive layer 10b has excellent hot water resistance, acid resistance, and alcohol resistance. An example of a commercially available crystalline polyester resin (a1) having a glass transition temperature Tg of −65° C. or lower is the above-mentioned product name “GM-913” (manufactured by TOYOBO Corporation).
[0038] The glass transition temperature Tg of the crystalline polyester resin (a1) can be measured, for example, by using a differential scanning calorimeter (DSC). More specifically, the glass transition temperature of a sample (crystalline polyester resin (a1)) can be determined from a DSC curve obtained by heating the sample from a temperature 30 K or more lower than the predicted glass transition temperature Tg to a temperature 30 K or more higher than the predicted glass transition temperature Tg at a heating rate of 5° C. / min while flowing nitrogen gas. The glass transition temperature Tg can be determined by determining the midpoint glass transition temperature based on the method described in JIS K7121:1987 "Method of measuring glass transition temperature of plastics."
[0039] The glass transition temperature Tg of the crystalline polyester resin (a1) may be −90° C. or higher, −80° C. or higher, or −75° C. or higher.
[0040] In order to achieve the effects of excellent hot water resistance, acid resistance, and alcohol resistance, the polyester resin (A) preferably contains 50 mass % or more of the crystalline polyester resin (a1), more preferably 60 mass % or more, more preferably 70 mass % or more, more preferably 80 mass % or more, and even more preferably 90 mass % or more. In order to particularly favorably exhibit the effects of excellent hot water resistance, acid resistance, and alcohol resistance, it is particularly preferred that the polyester resin (A) is entirely composed of the crystalline polyester resin (a1), i.e., it is particularly preferred that the polyester resin (A) contains 100% by mass of the crystalline polyester resin (a1).
[0041] The crystalline polyester resin (a1) preferably has a number average molecular weight Mn of more than 30,000, more preferably 31,000 or more, more preferably 32,000 or more, more preferably 33,000 or more, and even more preferably 34,000 or more. The crystalline polyester resin (a1) has a number average molecular weight Mn of preferably 40,000 or less, more preferably 39,000 or less, more preferably 38,000 or less, more preferably 37,000 or less, and even more preferably 36,000 or less. In the hot melt adhesive sheet 10 according to this embodiment, the adhesive layer 10b contains the crystalline polyester resin (a1) having the number average molecular weight Mn as described above. As a result, after the adhesive layer 10b is bonded to the first exposed surface and the third exposed surface of the solid electrolyte membrane 201, the adhesive layer 10b can sufficiently embed the outer edge of the solid electrolyte membrane 201, and can prevent the thickness from becoming uneven. In addition, the adhesive layer 10b has excellent hot water resistance, acid resistance, and alcohol resistance.
[0042] The number average molecular weight Mn of the crystalline polyester resin (a1) can be measured by gel permeation chromatography (GPC). The number average molecular weight Mn of the crystalline polyester resin (a1) can be measured, for example, using the following device and conditions. Measurement equipment and conditions ·Equipment: Product name "HLC-8020" (manufactured by Tosoh Corporation) Columns: Product names "TSKgel G2000HXL", "TSKgel G3000HXL", "TSKgel G4000HXL" (all manufactured by Tosoh Corporation) Solvent: THF ·Flow rate: 1.0mL / min Sample concentration: 2g / L ·Injection volume: 100μL ·Temperature: 40℃ Detector: Model number "RI-8020" (Tosoh Corporation) Standard material: TSK standard polystyrene (manufactured by Tosoh Corporation)
[0043] The crystalline polyester resin (a1) preferably has a melt viscosity of 2,000 dPa·s or more at 200°C, more preferably has a melt viscosity of 3,000 dPa·s or more, even more preferably has a melt viscosity of 4,000 dPa·s or more, still more preferably has a melt viscosity of 5,000 dPa·s or more, and still more preferably has a melt viscosity of 6,000 dPa·s or more. The crystalline polyester resin (a1) preferably has a melt viscosity of 10,000 dPa·s or less at 200°C, more preferably has a melt viscosity of 9,000 dPa·s or less, even more preferably has a melt viscosity of 8,000 dPa·s or less, and still more preferably has a melt viscosity of 7,000 dPa·s or less. In the hot melt adhesive sheet 10 according to this embodiment, the adhesive layer 10b contains the crystalline polyester resin (a1) having the melt viscosity as described above. This allows the adhesive layer 10b to fully embed the outer edge of the solid electrolyte membrane 201 after being adhered to the first exposed surface and the third exposed surface of the solid electrolyte membrane 201, thereby preventing the thickness from becoming uneven. In addition, the adhesive layer 10b has excellent hot water resistance, acid resistance, and alcohol resistance.
[0044] The melt viscosity of the crystalline polyester resin (a1) was measured using a micro compounder (manufactured by Thermo, product name "HAAKE MiniLab II") at 200°C for 100 min. -1 × 1 min.
[0045] (Epoxy resin (B)) As described above, the epoxy resin (B) contains the bisphenol type epoxy resin (b1) and the rubber-modified epoxy resin (b2).
[0046] Examples of the bisphenol type epoxy resin (b1) include bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol AD type epoxy resin. The bisphenol type epoxy resin (b1) may be modified. That is, the bisphenol type epoxy resin (b1) may be a modified bisphenol A type epoxy resin, a modified bisphenol F type epoxy resin, or a modified bisphenol AD type epoxy resin. As described above, the epoxy equivalent of the bisphenol type epoxy resin (b1) is 450 g / eq or more and 1000 g / eq or less. The epoxy equivalent can be determined in accordance with JIS K 7236.
[0047] As the bisphenol type epoxy resin (b1), it is preferable to use the bisphenol A type epoxy resin. Commercially available examples of such bisphenol A type epoxy resins include those manufactured by Mitsubishi Chemical Corporation under the trade names "jER 1001," "jER 1002," "jER 1003," "jER 1055," "jER 1004," and "jER 1004AF."
[0048] The bisphenol type epoxy resin (b1) may be contained in an amount of 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more relative to 100 parts by mass of the polyester resin (A). The bisphenol type epoxy resin (b1) may be contained in an amount of 50 parts by mass or less, 40 parts by mass or less, or 30 parts by mass or less, relative to 100 parts by mass of the polyester resin (A).
[0049] The rubber-modified epoxy resin (b2) is not particularly limited as long as it is a compound having at least one epoxy group in the molecule and having a structure derived from rubber, and various known rubber-modified epoxy resins can be used. The rubber-modified epoxy resin (b2) may be used alone or in combination of two or more kinds. The rubber-modified epoxy resin (b2) may be, for example, a reaction product of an epoxy resin with rubber. As the epoxy resin, for example, the above-mentioned bisphenol type epoxy resin (b1) can be used.
[0050] Examples of the rubber include natural rubber, acrylonitrile butadiene rubber (NBR), carboxyl-terminated acrylonitrile butadiene rubber (CTBN), amino-terminated acrylonitrile butadiene rubber (ATBN), styrene butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR), ethylene propylene rubber (EPDM), acrylic rubber (ACM), butyl rubber (IIR), and butadiene rubber. From the viewpoint of reactivity with epoxy groups, the rubber preferably has a functional group capable of reacting with epoxy groups, such as an amino group, a hydroxyl group or a carboxyl group, at its terminal.
[0051] From the viewpoints of easy availability and reactivity with epoxy groups, the rubber-modified epoxy resin (b2) is preferably a reaction product of an epoxy resin and an acrylonitrile butadiene rubber (NBR) (NBR-modified epoxy resin), a reaction product of an epoxy resin and a carboxyl-terminated acrylonitrile butadiene rubber (CTBN-modified epoxy resin), or a reaction product of an epoxy resin and an amino-terminated acrylonitrile butadiene rubber (ATBN-modified epoxy resin), and among these, an NBR-modified epoxy resin is particularly preferred. An example of a commercially available product of the NBR modified epoxy resin is "ADEKA RESIN EPR-1415-1" manufactured by ADEKA CORPORATION. The method for producing the rubber-modified epoxy resin (b2) is not particularly limited as long as it is a method that can react the epoxy resin with the rubber, and various known production methods can be adopted.
[0052] The physical properties of the rubber-modified epoxy resin (b2) are not particularly limited, but from the standpoint of handling properties and adhesive properties, it is preferable that the epoxy equivalent is 150 g / eq or more and 1000 g / eq or less. In the rubber-modified epoxy resin (b2), the epoxy equivalent can be determined in accordance with JIS K 7236.
[0053] The rubber-modified epoxy resin (b2) may be contained in an amount of 3 parts by mass or more, 5 parts by mass or more, or 7 parts by mass or more per 100 parts by mass of the polyester resin (A). The rubber-modified epoxy resin (b2) may be contained in an amount of 20 parts by mass or less, 15 parts by mass or less, or 10 parts by mass or less, per 100 parts by mass of the polyester resin (A).
[0054] The mass ratio of the rubber-modified epoxy resin (b2) to the bisphenol-type epoxy resin (b1) may be 20% or more, 25% or more, or 30% or more. Furthermore, the mass ratio of the rubber-modified epoxy resin (b2) to the bisphenol-type epoxy resin (b1) may be 50% or less, 45% or less, or 40% or less.
[0055] (Isocyanate-based crosslinking agent (C)) The isocyanate-based crosslinking agent (C) is not particularly limited, but may be any of the known crosslinking agents that have been used in the past, such as isocyanurates, biuret bodies, adducts, and polymeric bodies having polyfunctional isocyanate groups. Examples of such polyisocyanates include a dimer of 2,4-toluylene diisocyanate, triphenylmethane triisocyanate, tris-(p-isocyanatophenyl)thiophosphite, polyfunctional aromatic isocyanates, polyfunctional aromatic aliphatic isocyanates, polyfunctional aliphatic isocyanates, fatty acid-modified polyfunctional aliphatic isocyanates, blocked polyisocyanates such as blocked polyfunctional aliphatic isocyanates, and polyisocyanate prepolymers.
[0056] Among these isocyanate-based crosslinking agents (C), diphenylmethane diisocyanate, tolylene diisocyanate and xylylene diisocyanate are preferred as aromatic crosslinking agents. Among the aliphatic ones, modified products such as hexamethylene diisocyanate and isophorone diisocyanate are preferred. The isocyanate crosslinking agent (C) preferably contains three or more isocyanate groups in one molecule. Furthermore, as the isocyanate-based crosslinking agent (C), a polymer of the above-mentioned polyisocyanate, an adduct with another compound, or a urethane prepolymer obtained by reacting a low molecular weight polyol with a polyamine so that the molecular terminal is an isocyanate is preferably used. Among the various isocyanate-based crosslinking agents (C) mentioned above, it is preferable to use xylylene diisocyanate. An example of a commercially available product of the xylylene diisocyanate is "Takenate D-110N" manufactured by Mitsui Takeda Chemicals.
[0057] As described above, in the adhesive layer 10b of the hot melt adhesive sheet 10 of this embodiment, the isocyanate-based crosslinking agent (C) may be contained in an amount of 3 parts by mass or more, 5 parts by mass or more, or 7 parts by mass or more per 100 parts by mass of the polyester resin (A). The isocyanate-based crosslinking agent (C) may be contained in an amount of 20 parts by mass or less, 15 parts by mass or less, or 12 parts by mass or less, per 100 parts by mass of the polyester resin (A).
[0058] Next, referring to FIG. 2, the present embodiment will be further explained by taking as an example a case in which the adherend to which the adhesive layer 10b of the hot melt adhesive sheet 10 of the present embodiment is adhered is a membrane electrode assembly (MEA) 20 of a polymer electrolyte fuel cell.
[0059] The adherend, a membrane electrode assembly (MEA) 20, is configured to allow hydrogen gas to pass from the negative electrode side to the positive electrode side and to react the hydrogen with oxygen supplied to the positive electrode side to generate electricity.
[0060] As shown in FIG. 2, in a membrane electrode assembly (MEA) 20, a positive electrode 202 and a negative electrode 203 are laminated on both opposing sides of a solid electrolyte membrane 201, respectively. The positive electrode 202 includes a positive electrode catalyst layer 202a and a positive electrode gas diffusion layer 202b laminated on the positive electrode catalyst layer 202a. The positive electrode catalyst layer 202a is laminated on one side of the solid electrolyte membrane 201. The negative electrode 203 includes a negative electrode catalyst layer 203 a and a negative electrode gas diffusion layer 203 b laminated on the negative electrode catalyst layer 203 a, and the negative electrode catalyst layer 203 a is laminated on the other side of the solid electrolyte membrane 201 .
[0061] As shown in FIG. 2, the positive electrode catalyst layer 202a and the negative electrode catalyst layer 203a are formed so as to have smaller planar dimensions than the solid electrolyte membrane 201, and the positive electrode gas diffusion layer 202b and the negative electrode gas diffusion layer 203b are also formed so as to have smaller planar dimensions than the positive electrode catalyst layer 202a and the negative electrode catalyst layer 203a. That is, in the membrane electrode assembly (MEA), the planar dimensions of the positive electrode 202 and the negative electrode 203 are smaller than the planar dimensions of the solid electrolyte membrane 201. As described above, the planar dimensions of the positive electrode 202 are smaller than the planar dimensions of the solid electrolyte membrane 201, and therefore, on the positive electrode side (one side) of the membrane electrode assembly (MEA) 20, a positive electrode-side electrolyte membrane exposed region 201a is formed on the outer periphery, where the solid electrolyte membrane 201 extends outward beyond the positive electrode catalyst layer 202a and the surface of the solid electrolyte membrane 201 is exposed. In addition, since the planar dimensions of the negative electrode 203 are smaller than the planar dimensions of the solid electrolyte membrane 201, a negative electrode side electrolyte membrane exposed region 201b is formed on the outer periphery of the negative electrode side (other side) of the membrane electrode assembly (MEA) 20, where the solid electrolyte membrane 201 extends outward beyond the negative electrode catalyst layer 203a and the surface of the solid electrolyte membrane 201 is exposed. The positive electrode side electrolyte membrane exposed region 201a corresponds to the above-mentioned first exposed surface, and the negative electrode side electrolyte membrane exposed region 201b corresponds to the above-mentioned third exposed surface.
[0062] In addition, on the positive electrode side of the membrane electrode assembly (MEA) 20, a positive electrode side catalyst layer exposed region 202a1 is formed where the positive electrode catalyst layer 202a extends outward beyond the positive electrode gas diffusion layer 202b and the surface of the positive electrode catalyst layer 202a is exposed. The positive electrode catalyst layer exposed region 202a1 is formed inside the positive electrode electrolyte membrane exposed region 201a and outside the positive electrode gas diffusion layer 202b. In this embodiment, the positive electrode side electrolyte membrane exposed region 201a is formed in an annular shape so as to go around the outer periphery of the membrane electrode assembly (MEA) 20. The positive electrode-side catalyst layer exposed region 202a1 is formed in an annular shape that is smaller than the positive electrode-side electrolyte membrane exposed region 201a. That is, on the positive electrode side of the membrane electrode assembly (MEA), a second boundary line L2, which is the boundary line between the positive electrode side electrolyte membrane exposed region 201a and the positive electrode side catalyst layer exposed region 202a1, is formed inside a first boundary line L1, which is the boundary line between the positive electrode side electrolyte membrane exposed region 201a and the positive electrode side catalyst layer exposed region 202a1. The positive electrode side catalyst layer exposed region 202a1 is the above-mentioned second exposed surface.
[0063] On the negative electrode side of the membrane electrode assembly (MEA) 20, a negative electrode side catalyst layer exposed region 203a1 is formed in which the negative electrode catalyst layer 203a extends outward beyond the negative electrode gas diffusion layer 203b, exposing the surface of the negative electrode catalyst layer 203a. The negative electrode catalyst layer exposed region 203a1 is formed inside the negative electrode electrolyte membrane exposed region 201b and outside the negative electrode gas diffusion layer 203b. In this embodiment, the negative electrode side electrolyte membrane exposed region 201b is formed in an annular shape so as to go around the outer periphery of the membrane electrode assembly (MEA) 20. The negative electrode-side catalyst layer exposed region 203a1 is formed in an annular shape smaller than the negative electrode-side electrolyte membrane exposed region 201b. That is, on the negative electrode side of the membrane electrode assembly (MEA) 20, a fourth boundary line L4, which is the boundary line between the negative electrode side electrolyte membrane exposed region 201b and the negative electrode side catalyst layer exposed region 203a1, is formed inside the third boundary line L3, which is the boundary line between the negative electrode side electrolyte membrane exposed region 201b and the negative electrode side catalyst layer exposed region 203a1. The negative electrode side catalyst layer exposed region 203a1 is the above-mentioned fourth exposed surface.
[0064] In the usage state shown in FIG. 2, two hot melt adhesive sheets 10, i.e., a first hot melt adhesive sheet 10 adhered to the positive electrode side of a membrane electrode assembly (MEA) 20 and a second hot melt adhesive sheet 10 adhered to the negative electrode side of the membrane electrode assembly (MEA) 20, are used as sub-gasket materials for a solid polymer fuel cell.
[0065] The first hot melt adhesive sheet 10 is annular and has a shape such that when it is overlaid on the membrane electrode assembly (MEA) 20, its outer peripheral edge is outside the membrane electrode assembly (MEA) 20, and its inner peripheral edge fits within the positive electrode side catalyst layer exposed region 202a1 and the negative electrode side catalyst layer exposed region 203a1. That is, the hollow portion of the first hot melt adhesive sheet 10 has a shape slightly larger than the positive electrode gas diffusion layer 202b.
[0066] The second hot melt adhesive sheet 10 has a shape similar to that of the first hot melt adhesive sheet 10 .
[0067] In this embodiment, the first hot melt adhesive sheet 10 and the second hot melt adhesive sheet 10 are directly bonded to each other at the outer periphery of the adhesive layer 10b outside the membrane electrode assembly (MEA) 20, and are used as the subgasket material.
[0068] The first hot melt adhesive sheet 10 has its inner periphery, other than the outer periphery adhered to the second hot melt adhesive sheet 10, adhered to the outer periphery of the membrane electrode assembly (MEA) 20, and is adhered in an area extending from the positive electrode side electrolyte membrane exposed region 201a (first exposed surface) across the first boundary line L1 to the positive electrode side catalyst layer exposed region 202a1 (second exposed surface). The second hot melt adhesive sheet 10 is adhered in the same manner as the first hot melt adhesive sheet 10.
[0069] By adhering (coating) the hot melt adhesive sheet 10 to the membrane electrode assembly (MEA) 20 as described above, a portion of the positive electrode gas can permeate through the positive electrode side electrolyte membrane exposed region 201a and a portion of the negative electrode gas can permeate through the negative electrode side electrolyte membrane exposed region 201b, thereby preventing a decrease in performance as a solid polymer fuel cell.
[0070] Here, the hot melt adhesive sheet 10 according to this embodiment is configured as described above. Therefore, as described above, after the first hot melt adhesive sheet 10 is adhered to the range from the positive electrode side electrolyte membrane exposed region 201a (first exposed surface) across the first boundary line L1 to the positive electrode side catalyst layer exposed region 202a1 (second exposed surface), and the second hot melt adhesive sheet 10 is adhered to the range from the negative electrode side electrolyte membrane exposed region 201b (third exposed surface) across the third boundary line L3 to the negative electrode side catalyst layer exposed region 203a1 (fourth exposed surface), the outer edge of the solid electrolyte membrane 201 is sufficiently embedded with the adhesive layer 10b, and the thickness of the adhesive layer 10b is prevented from becoming uneven. Specifically, even if the first hot melt adhesive sheet 10 and the second hot melt adhesive sheet 10 are held for 500 hours in an atmosphere of 95°C while a load of 7.5 MPa is applied from the outer side (substrate 10a side) of each of the first hot melt adhesive sheet 10 and the second hot melt adhesive sheet 10 via a metal gasket, the outer edge of the solid electrolyte membrane 201 can be sufficiently embedded by the adhesive layer 10b and the thickness of the adhesive layer 10b can be prevented from becoming uneven.
[0071] As described above, in a polymer electrolyte fuel cell, hydrogen and oxygen react with each other in the membrane electrode assembly (MEA) 20 to generate electricity. When hydrogen and oxygen react as described above, the membrane electrode assembly (MEA) 20 reaches a relatively high temperature (for example, 95° C.). When the solid polymer fuel cell is installed in an automobile as a power source, the central portion of the membrane / electrode assembly (MEA) 20 is sufficiently cooled by circulating antifreeze liquid contained in a radiator through a pipeline. However, since the pipeline is usually not extended to the edge portions of the membrane / electrode assembly (MEA) 20, the edge portions of the membrane / electrode assembly (MEA) 20 continue to maintain a high temperature.
[0072] Furthermore, when the antifreeze liquid is circulated, a portion of the antifreeze liquid may leak out of the pipeline, and the antifreeze liquid leaking from the pipeline may come into contact with the adhesive layer 10b attached to the edge side of the solid electrolyte membrane 201. The antifreeze liquid normally contains polyethylene glycol and water as liquid components, and therefore in such a case, the adhesive layer 10b is in a state of contact with polyethylene glycol and water at high temperatures.
[0073] Furthermore, in the reaction in which electricity is generated, hydrogen ions (H + ) undergoes mass transfer, so that the membrane electrode assembly (MEA) 20 exhibits strong acidity equivalent to about 0.1 to 0.5M dilute sulfuric acid. In such a case, the adhesive layer 10b attached to the edge side of the solid electrolyte membrane 201 is exposed to a strong acidic environment at high temperatures.
[0074] Here, in the hot melt adhesive sheet 10 according to this embodiment, the adhesive layer 10b contains the crystalline polyester resin (a1) having the above-mentioned physical properties, and therefore the adhesive layer 10b has excellent hot water resistance, acid resistance, and alcohol resistance. Therefore, when the hot melt adhesive sheet 10 configured in this manner is used as a sub-gasket material in a solid polymer fuel cell mounted on an automobile, as described above, even if the adhesive layer 10b comes into contact with water or alcohol at a high temperature such as 95°C, or is exposed to strong acidity at a high temperature such as 95°C, the adhesive layer 10b can maintain its adhesion to the solid electrolyte membrane 201 for a long period of time (1000 hours). As will be described later, the solid electrolyte membrane 201 is usually made of a fluororesin such as perfluorocarbon sulfonic acid.
[0075] In the membrane electrode assembly (MEA) 20, the positive electrode catalyst layer 202 a and the negative electrode catalyst layer 203 a are generally formed using a catalyst ink composition containing a catalyst support material such as a carbon material supporting a catalyst, a proton conductive polymer, and a solvent.
[0076] The solid electrolyte membrane 201 of the membrane electrode assembly (MEA) 20 is formed of, for example, a fluororesin such as a perfluorocarbon sulfonic acid resin. Examples of the perfluorocarbon sulfonic acid resin include "Nafion" (trade name) manufactured by DuPont, "Flemion" (trade name) manufactured by Asahi Kasei Corporation, and "Aciplex" (trade name) manufactured by Asahi Glass Co., Ltd. The perfluorocarbon sulfonic acid resin is, for example, a resin having a polymer structure represented by the following formula (1). Regarding m, n, and x in the following formula (1), for example, in the "Nafion", m≧1, n=2, x=5 to 13.5; in the "Aciplex", m=0,1, n=2 to 5, x=1.5 to 14; and in the "Flemion", m=0,1, n=1 to 5.
[0077] [ka]
[0078] The positive electrode catalyst layer 202a and the negative electrode catalyst layer 203a are layers containing catalyst particles. The catalyst particles contained in the positive electrode catalyst layer 202a include platinum. The catalyst particles contained in the negative electrode catalyst layer 203a include a platinum compound. The platinum compound includes an alloy of platinum and at least one metal selected from the group consisting of ruthenium, palladium, nickel, molybdenum, iridium, and iron.
[0079] The positive electrode gas diffusion layer 202b and the negative electrode gas diffusion layer 203b are made of a porous conductive base material. Examples of the porous conductive substrate include carbon paper and carbon cloth.
[0080] The hot melt adhesive sheet 10 according to this embodiment can also be used in a redox flow battery. Hot melt adhesive sheets used in redox flow batteries are used to prevent electrolyte permeation.
[0081] The matters disclosed in this specification include the following.
[0082] (1) A hot melt adhesive sheet having an adhesive layer formed of a hot melt adhesive laminated on at least one surface of a substrate, The hot melt adhesive includes a crosslinked product of an adhesive composition including a crosslinking agent, the adhesive composition including a polyester resin, an epoxy resin, and an isocyanate-based crosslinking agent; The epoxy resin includes a bisphenol type epoxy resin and a rubber-modified epoxy resin, The bisphenol type epoxy resin has an epoxy equivalent of 450 g / eq or more and 1000 g / eq or less. Hot melt adhesive sheet.
[0083] (2) The polyester resin includes a crystalline polyester resin having a softening point of 120° C. or higher. The hot melt adhesive sheet according to (1) above.
[0084] (3) The bisphenol type epoxy resin includes a bisphenol A type epoxy resin. The hot melt adhesive sheet according to (1) or (2) above.
[0085] (4) The rubber-modified epoxy resin is an NBR-modified epoxy resin. A hot melt adhesive sheet according to any one of (1) to (3) above.
[0086] (5) Used by adhering to the solid electrolyte membrane of polymer electrolyte fuel cells A hot melt adhesive sheet according to any one of (1) to (4) above.
[0087] The hot melt adhesive sheet according to the present invention is not limited to the above-mentioned embodiment. The hot melt adhesive sheet according to the present invention is also not limited by the above-mentioned action and effect. The hot melt adhesive sheet according to the present invention can be modified in various ways without departing from the gist of the present invention. EXAMPLES
[0088] [Dissolution example of bisphenol type epoxy resin (b1)] <Dissolution example of bisphenol type epoxy resin (b1): B1> A reaction vessel equipped with a stirrer, a reflux condenser, a thermometer, a nitrogen inlet tube, and a manhole was prepared. While replacing the inside of the reaction vessel with nitrogen, 400.0 g of bisphenol A type epoxy resin (epoxy equivalent: 450 to 500 g / eq, jER1001: manufactured by Mitsubishi Chemical Corporation. Hereinafter, referred to as epoxy resin B1) was charged, and 600.0 g of methyl ethyl ketone (MEK) was charged as a solvent while stirring. The temperature inside the system was then raised to 60° C. to completely dissolve the epoxy resin B1 in the methyl ethyl ketone. As a result, a solution BB1 of the epoxy resin B1 (hereinafter referred to as epoxy resin solution BB1) was obtained. The solid content of the obtained epoxy resin solution BB1 was 40 mass %.
[0089] <Dissolution example of bisphenol type epoxy resin (b1): B2> A solution BB2 of epoxy resin B2 (hereinafter referred to as epoxy resin solution BB2) was obtained in the same manner as in dissolution example B1, except that a bisphenol A type epoxy resin (epoxy equivalent: 670 to 770 g / eq, jER1003: manufactured by Mitsubishi Chemical Corporation. Hereinafter referred to as epoxy resin B2) was used instead of epoxy resin B1. The solid content of the obtained epoxy resin solution BB2 was 40 mass %.
[0090] <Dissolution example of bisphenol type epoxy resin (b1): B3> A solution BB3 of epoxy resin B3 (hereinafter referred to as epoxy resin solution BB3) was obtained in the same manner as in dissolution example B1, except that a bisphenol A type epoxy resin (epoxy equivalent: 875 to 975 g / eq, jER1004: manufactured by Mitsubishi Chemical Corporation. Hereinafter referred to as epoxy resin B3) was used instead of epoxy resin B1. The solid content of the obtained epoxy resin solution BB3 was 40 mass %.
[0091] <Dissolution example of bisphenol type epoxy resin (b1): B4> A solution BB4 of epoxy resin B4 (hereinafter referred to as epoxy resin solution B4) was obtained in the same manner as in dissolution example B1, except that a bisphenol A type epoxy resin (epoxy equivalent: 1,750 to 2,200 g / eq, jER1007: manufactured by Mitsubishi Chemical Corporation. Hereinafter referred to as epoxy resin B4) was used instead of epoxy resin B1.
[0092] <Dissolution example of bisphenol type epoxy resin (b1): B5> A solution BB5 of epoxy resin B5 (hereinafter referred to as epoxy resin solution B5) was obtained in the same manner as in dissolution example B1, except that bisphenol A type phenoxy resin (epoxy equivalent: 7,500 to 8,500 g / eq, jER1256: manufactured by Mitsubishi Chemical Corporation. Hereinafter referred to as epoxy resin B5) was used instead of epoxy resin B1.
[0093] <Dissolution example of bisphenol type epoxy resin (b1): B6> A solution BB6 of epoxy resin B6 (hereinafter referred to as epoxy resin solution BB6) was obtained in the same manner as in dissolution example B1, except that a bisphenol A novolac type epoxy resin (epoxy equivalent: 200 to 220 g / eq, jER157S70: manufactured by Mitsubishi Chemical Corporation; referred to as epoxy resin B6) was used instead of epoxy resin B1.
[0094] Example 1 To the epoxy resin solution BB1, a first urethane-modified polyester resin (manufactured by TOYOBO under the trade name "Vylon (registered trademark) UR-3210") as the polyester resin (A), a rubber-modified epoxy resin (b2) (manufactured by ADEKA under the trade name "ADEKA RESIN EPR-1415-1"), and an isocyanate-based crosslinking agent (C) (manufactured by Mitsui Takeda Chemical under the trade name "Takenate D-110N") were added in the blending ratios shown in Table 1A below to obtain a hot melt adhesive layer composition according to Example 1. The urethane-modified polyester resin ("UR-3210") was added to the epoxy resin solution BB1 as follows. That is, a solution (hereinafter referred to as the first urethane-modified polyester resin solution) was prepared by dissolving the first urethane-modified polyester resin at 25 mass% in a mixed solvent obtained by mixing toluene and methyl ethyl ketone in a mass ratio of toluene:methyl ethyl ketone = 8:2, and then the first urethane-modified polyester resin solution was added to the epoxy resin solution BB1.
[0095] Example 2 A composition for a hot melt adhesive layer according to Example 2 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB2 was used instead of the epoxy resin solution BB1.
[0096] Example 3 A composition for a hot melt adhesive layer according to Example 3 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB3 was used instead of the epoxy resin solution BB1.
[0097] Example 4 The composition for hot melt adhesive layer of Example 4 was obtained in the same manner as Example 1, except that a second urethane-modified polyester resin (manufactured by TOYOBO Corporation under the trade name "Vylon (registered trademark) UR-4410") was used as the polyester resin (A) instead of the first urethane-modified polyester resin. The second urethane-modified polyester resin was prepared in the same manner as in Example 1, and added to the epoxy resin solution BB1 in the form of a second urethane-modified polyester resin solution.
[0098] Example 5 A composition for hot melt adhesive layer of Example 5 was obtained in the same manner as in Example 1, except that epoxy resin solution BB2 was used instead of epoxy resin solution BB1, and the second urethane-modified polyester resin was used instead of the first urethane-modified polyester resin. The second urethane-modified polyester resin was added to the epoxy resin solution BB2 in the same manner as in Example 4.
[0099] Example 6 A composition for hot melt adhesive layer of Example 6 was obtained in the same manner as in Example 1, except that epoxy resin solution BB3 was used instead of epoxy resin solution BB1, and the second urethane-modified polyester resin was used instead of the first urethane-modified polyester resin. The second urethane-modified polyester resin was added to the epoxy resin solution BB3 in the same manner as in Example 4.
[0100] Example 7 A composition for a hot melt adhesive layer according to Example 7 was obtained in the same manner as in Example 1, except that a first crystalline polyester resin (manufactured by TOYOBO Corporation under the trade name "GM-920") was used instead of the first urethane-modified polyester resin. The first crystalline polyester resin was prepared in the same manner as in Example 1 and added to the epoxy resin solution BB1 in the form of a first crystalline polyester resin solution.
[0101] Example 8 A composition for hot melt adhesive layer of Example 8 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB2 was used instead of the epoxy resin solution BB1, and the first crystalline polyester resin was used instead of the first urethane-modified polyester resin. The first crystalline polyester resin was added to the epoxy resin solution BB2 in the same manner as in Example 7.
[0102] Example 9 A composition for hot melt adhesive layer of Example 9 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB3 was used instead of the epoxy resin solution BB1, and the first crystalline polyester resin was used instead of the first urethane-modified polyester resin. The first crystalline polyester resin was added to the epoxy resin solution BB3 in the same manner as in Example 7.
[0103] Example 10 A composition for hot melt adhesive layer of Example 10 was obtained in the same manner as Example 1, except that a second crystalline polyester resin (manufactured by TOYOBO Corporation under the trade name "GM-913") was used instead of the first urethane-modified polyester resin. The second crystalline polyester resin was prepared in the same manner as in Example 1, and added to the epoxy resin solution BB1 in the form of a second crystalline polyester resin solution.
[0104] Example 11 A composition for hot melt adhesive layer of Example 11 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB2 was used instead of the epoxy resin solution BB1, and the second crystalline polyester resin was used instead of the first urethane-modified polyester resin. The second crystalline polyester resin was added to the epoxy resin solution BB2 in the same manner as in Example 10.
[0105] Example 12 A composition for hot melt adhesive layer of Example 12 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB3 was used instead of the epoxy resin solution BB1, and the second crystalline polyester resin was used instead of the first urethane-modified polyester resin. The second crystalline polyester resin was added to the epoxy resin solution BB3 in the same manner as in Example 10.
[0106] Example 13 A composition for a hot melt adhesive layer according to Example 13 was obtained in the same manner as in Example 1, except that a third crystalline polyester resin (manufactured by Unitika Ltd. under the trade name "UE-9400") was used instead of the first urethane-modified polyester resin. The third crystalline polyester resin was prepared in the same manner as in Example 1, and added to the epoxy resin solution BB1 in the form of a third crystalline polyester resin solution.
[0107] Example 14 A composition for a hot melt adhesive layer according to Example 14 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB2 was used instead of the epoxy resin solution BB1, and the third crystalline polyester resin was used instead of the first urethane-modified polyester resin. The third crystalline polyester resin was added to the epoxy resin solution BB2 in the same manner as in Example 13.
[0108] Example 15 A hot melt adhesive layer composition of Example 15 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB3 was used instead of the epoxy resin solution BB1, and the third crystalline polyester resin was used instead of the first urethane-modified polyester resin. The third crystalline polyester resin was added to the epoxy resin solution BB3 in the same manner as in Example 13.
[0109] (Example 16) A composition for a hot melt adhesive layer according to Example 16 was obtained in the same manner as in Example 1, except that a fourth crystalline polyester resin (manufactured by Unitika Ltd. under the trade name "UE-3400") was used instead of the first urethane-modified polyester resin. The fourth crystalline polyester resin was prepared in the same manner as in Example 1, and added to the epoxy resin solution BB1 in the form of a fourth crystalline polyester resin solution.
[0110] (Example 17) A composition for hot melt adhesive layer of Example 17 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB2 was used instead of the epoxy resin solution BB1, and the fourth crystalline polyester resin was used instead of the first urethane-modified polyester resin. The fourth crystalline polyester resin was added to the epoxy resin solution BB2 in the same manner as in Example 16.
[0111] (Example 18) A composition for hot melt adhesive layer of Example 18 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB3 was used instead of the epoxy resin solution BB1, and the fourth crystalline polyester resin was used instead of the first urethane-modified polyester resin. The fourth crystalline polyester resin was added to the epoxy resin solution BB3 in the same manner as in Example 16.
[0112] (Example 19) A composition for a hot melt adhesive layer according to Example 19 was obtained in the same manner as in Example 1, except that a fifth crystalline polyester resin (manufactured by Unitika Ltd. under the trade name "UE-3410") was used instead of the first urethane-modified polyester resin. The fifth crystalline polyester resin was prepared in the same manner as in Example 1, and added to the epoxy resin solution BB1 in the form of a fifth crystalline polyester resin solution.
[0113] (Example 20) A composition for hot melt adhesive layer of Example 20 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB2 was used instead of the epoxy resin solution BB1, and the fifth crystalline polyester resin was used instead of the first urethane-modified polyester resin. The fifth crystalline polyester resin was added to the epoxy resin solution BB2 in the same manner as in Example 19.
[0114] Example 21 A hot melt adhesive composition of Example 21 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB3 was used instead of the epoxy resin solution BB1, and the fifth crystalline polyester resin was used instead of the first urethane-modified polyester resin. The fifth crystalline polyester resin was added to the epoxy resin solution BB3 in the same manner as in Example 19.
[0115] [Table 1A]
[0116] Comparative Example 1 A composition for a hot melt adhesive layer according to Comparative Example 1 was obtained in the same manner as in Example 1, except that the rubber-modified epoxy resin (b2) was not added.
[0117] Comparative Example 2 A composition for a hot melt adhesive layer according to Comparative Example 2 was obtained in the same manner as in Example 2, except that the rubber-modified epoxy resin (b2) was not added.
[0118] Comparative Example 3 A composition for a hot melt adhesive layer according to Comparative Example 3 was obtained in the same manner as in Example 3, except that the rubber-modified epoxy resin (b2) was not added.
[0119] Comparative Example 4 A composition for a hot melt adhesive layer according to Comparative Example 4 was obtained in the same manner as in Example 4, except that the rubber-modified epoxy resin (b2) was not added.
[0120] Comparative Example 5 A composition for a hot melt adhesive layer according to Comparative Example 5 was obtained in the same manner as in Example 5, except that the rubber-modified epoxy resin (b2) was not added.
[0121] Comparative Example 6 A composition for a hot melt adhesive layer according to Comparative Example 6 was obtained in the same manner as in Example 6, except that the rubber-modified epoxy resin (b2) was not added.
[0122] Comparative Example 7 A composition for a hot melt adhesive layer according to Comparative Example 7 was obtained in the same manner as in Example 7, except that the rubber-modified epoxy resin (b2) was not added.
[0123] Comparative Example 8 A composition for a hot melt adhesive layer according to Comparative Example 8 was obtained in the same manner as in Example 8, except that the rubber-modified epoxy resin (b2) was not added.
[0124] Comparative Example 9 A composition for a hot melt adhesive layer according to Comparative Example 9 was obtained in the same manner as in Example 9, except that the rubber-modified epoxy resin (b2) was not added.
[0125] Comparative Example 10 A composition for a hot melt adhesive layer according to Comparative Example 10 was obtained in the same manner as in Example 10, except that the rubber-modified epoxy resin (b2) was not added.
[0126] Comparative Example 11 A composition for a hot melt adhesive layer according to Comparative Example 11 was obtained in the same manner as in Example 11, except that the rubber-modified epoxy resin (b2) was not added.
[0127] Comparative Example 12 A composition for a hot melt adhesive layer according to Comparative Example 12 was obtained in the same manner as in Example 12, except that the rubber-modified epoxy resin (b2) was not added.
[0128] Comparative Example 13 A composition for a hot melt adhesive layer according to Comparative Example 13 was obtained in the same manner as in Example 13, except that the rubber-modified epoxy resin (b2) was not added.
[0129] (Comparative Example 14) A composition for a hot melt adhesive layer according to Comparative Example 14 was obtained in the same manner as in Example 14, except that the rubber-modified epoxy resin (b2) was not added.
[0130] Comparative Example 15 A composition for a hot melt adhesive layer according to Comparative Example 15 was obtained in the same manner as in Example 15, except that the rubber-modified epoxy resin (b2) was not added.
[0131] Comparative Example 16 A composition for a hot melt adhesive layer according to Comparative Example 16 was obtained in the same manner as in Example 16, except that the rubber-modified epoxy resin (b2) was not added.
[0132] (Comparative Example 17) A composition for a hot melt adhesive layer according to Comparative Example 17 was obtained in the same manner as in Example 17, except that the rubber-modified epoxy resin (b2) was not added.
[0133] (Comparative Example 18) A composition for a hot melt adhesive layer according to Comparative Example 18 was obtained in the same manner as in Example 18, except that the rubber-modified epoxy resin (b2) was not added.
[0134] Comparative Example 19 A composition for a hot melt adhesive layer according to Comparative Example 19 was obtained in the same manner as in Example 19, except that the rubber-modified epoxy resin (b2) was not added.
[0135] (Comparative Example 20) A composition for a hot melt adhesive layer according to Comparative Example 20 was obtained in the same manner as in Example 20, except that the rubber-modified epoxy resin (b2) was not added.
[0136] Comparative Example 21 A composition for a hot melt adhesive layer according to Comparative Example 21 was obtained in the same manner as in Example 21, except that the rubber-modified epoxy resin (b2) was not added.
[0137] The formulations of the compositions for hot melt adhesive layers according to Comparative Examples 1 to 21 are shown in Table 1B below.
[0138] [Table 1B]
[0139] Comparative Example 22 A composition for a hot melt adhesive layer according to Comparative Example 22 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB4 was used instead of the epoxy resin solution BB1.
[0140] (Comparative Example 23) A composition for a hot melt adhesive layer according to Comparative Example 23 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB5 was used instead of the epoxy resin solution BB1.
[0141] Comparative Example 24 A composition for a hot melt adhesive layer according to Comparative Example 24 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB6 was used instead of the epoxy resin solution BB1.
[0142] Comparative Example 25 A composition for hot melt adhesive layer relating to Comparative Example 25 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB4 was used instead of the epoxy resin solution BB1, and the second urethane-modified polyester resin was used instead of the first urethane-modified polyester resin.
[0143] Comparative Example 26 A composition for hot melt adhesive layer relating to Comparative Example 26 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB5 was used instead of the epoxy resin solution BB1, and the second urethane-modified polyester resin was used instead of the first urethane-modified polyester resin.
[0144] (Comparative Example 27) A composition for hot melt adhesive layer relating to Comparative Example 27 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB6 was used instead of the epoxy resin solution BB1, and the second urethane-modified polyester resin was used instead of the first urethane-modified polyester resin.
[0145] (Comparative Example 28) A composition for hot melt adhesive layer relating to Comparative Example 28 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB4 was used instead of the epoxy resin solution BB1, and the first crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0146] Comparative Example 29 A composition for hot melt adhesive layer relating to Comparative Example 29 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB5 was used instead of the epoxy resin solution BB1, and the first crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0147] (Comparative Example 30) A composition for hot melt adhesive layer according to Comparative Example 30 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB6 was used instead of the epoxy resin solution BB1, and the first crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0148] (Comparative Example 31) A composition for hot melt adhesive layer according to Comparative Example 31 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB4 was used instead of the epoxy resin solution BB1, and the second crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0149] (Comparative Example 32) A composition for hot melt adhesive layer relating to Comparative Example 32 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB5 was used instead of the epoxy resin solution BB1, and the second crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0150] (Comparative Example 33) A composition for hot melt adhesive layer according to Comparative Example 33 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB6 was used instead of the epoxy resin solution BB1, and the second crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0151] (Comparative Example 34) A composition for hot melt adhesive layer relating to Comparative Example 34 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB4 was used instead of the epoxy resin solution BB1, and the third crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0152] (Comparative Example 35) A composition for hot melt adhesive layer relating to Comparative Example 35 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB5 was used instead of the epoxy resin solution BB1, and the third crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0153] (Comparative Example 36) A composition for hot melt adhesive layer according to Comparative Example 36 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB6 was used instead of the epoxy resin solution BB1, and the third crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0154] (Comparative Example 37) A composition for hot melt adhesive layer relating to Comparative Example 37 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB4 was used instead of the epoxy resin solution BB1, and the fourth crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0155] (Comparative Example 38) A composition for hot melt adhesive layer relating to Comparative Example 38 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB5 was used instead of the epoxy resin solution BB1, and the fourth crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0156] (Comparative Example 39) A composition for hot melt adhesive layer relating to Comparative Example 39 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB6 was used instead of the epoxy resin solution BB1, and the fourth crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0157] (Comparative Example 40) A composition for hot melt adhesive layer relating to Comparative Example 40 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB4 was used instead of the epoxy resin solution BB1, and the fifth crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0158] (Comparative Example 41) A composition for hot melt adhesive layer relating to Comparative Example 41 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB5 was used instead of the epoxy resin solution BB1, and the fifth crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0159] (Comparative Example 42) A composition for hot melt adhesive layer relating to Comparative Example 42 was obtained in the same manner as in Example 1, except that the epoxy resin solution BB6 was used instead of the epoxy resin solution BB1, and the sixth crystalline polyester resin was used instead of the first urethane-modified polyester resin.
[0160] The formulations of the compositions for hot melt adhesive layers according to Comparative Examples 22 to 42 are shown in Table 1C below.
[0161] [Table 1C]
[0162] In addition, the various physical properties of the various polyester resins (A) (first urethane-modified polyester resin (UR-3210), second urethane-modified polyester resin (UR-4410), first crystalline polyester resin (GM-920), second crystalline polyester resin (GM-913), third crystalline polyester resin (UE-9400), fourth crystalline polyester resin (UE-3400), and fifth crystalline polyester resin (UE-3410)) blended in the hot melt adhesive layer composition of each example are shown in Table 2 below.
[0163] [Table 2]
[0164] [Coating of the composition for hot melt adhesive layer] The hot melt adhesive layer composition according to each of the Examples and Comparative Examples was diluted with methyl ethyl ketone (MEK) so that the solid content was 30 mass %. Next, a PEN film with a hot melt adhesive layer was obtained for each of the Examples and Comparative Examples according to the following procedure. (1) The diluted hot melt adhesive layer composition is applied to the entire surface of one side of a PEN film (length: 210 mm, width: 150 mm, thickness: 100 μm, Teonex: manufactured by Toyobo Film Solutions Co., Ltd.). The coating is carried out so that the dried thickness of the hot melt adhesive layer composition becomes 20 μm. (2) The PEN film coated with the diluted hot melt adhesive layer composition is dried at 100° C. for 1 minute to obtain a PEN film having a dried product of the hot melt adhesive layer composition. (3) The PEN film having the dried hot melt adhesive layer composition is left in an oven at 40° C. for 48 hours to allow the curing reaction (crosslinking reaction) to proceed, thereby obtaining a PEN film having a hot melt adhesive layer.
[0165] (Hot melt adhesive layer thickness retention rate) The PEN films with hot melt adhesive layers according to each Example and the PEN films with hot melt adhesive layers according to each Comparative Example were evaluated for the retention of the thickness of the hot melt adhesive layer after being adhered to the solid electrolyte membrane of a polymer electrolyte fuel cell. In this evaluation, a membrane electrode assembly (MEA) 20 of a polymer electrolyte fuel cell, as shown in FIG. 2, was used as the adherend. The PEN film with the hot melt adhesive layer according to each of the Examples and Comparative Examples was adhered to the membrane electrode assembly (MEA) 20 as an adherend according to the following procedure. It should be noted that a description of the configuration of the membrane electrode assembly (MEA) 20 will be omitted. Adhesion Procedure (1) For each of the examples and comparative examples, two PEN films with a hot melt adhesive layer were prepared. In each of the examples and comparative examples, the PEN film with the hot melt adhesive layer is annular in shape, and when it is overlaid on the membrane electrode assembly (MEA) 20, its outer peripheral edge is outside the membrane electrode assembly (MEA) 20, and its inner peripheral edge is shaped to fit within the positive electrode side catalyst layer exposed region 202a1 and the negative electrode side catalyst layer exposed region 203a1. That is, in each of the examples and comparative examples, the hollow portion of the PEN film with the hot melt adhesive layer has a shape slightly larger than the positive electrode gas diffusion layer 202b and the negative electrode gas diffusion layer 203b. (2) A PEN film with a hot melt adhesive layer is brought into contact with the entire positive electrode-side electrolyte membrane exposed region 201a and a part of the positive electrode-side catalyst layer exposed region 202a1. Also, another PEN film with a hot melt adhesive layer is brought into contact with the entire negative electrode electrolyte membrane exposed region 201b and a part of the negative electrode catalyst layer exposed region 203a1. This results in a specimen in which two PEN films with hot melt adhesive layers are bonded to the membrane electrode assembly (MEA) 20. (3) After exposing the test specimen to an atmosphere at 95°C, a pair of metal gaskets are each placed against the central portions of the exposed surfaces of the PEN film with one hot melt adhesive layer and the PEN film with the other hot melt adhesive layer. Thereafter, the test specimen is exposed to an atmosphere at 95° C. and maintained for 500 hours while a load of 7.5 MPa is applied to the test specimen via the pair of metal gaskets. As a result, the PEN film with one hot melt adhesive layer and the PEN film with the other hot melt adhesive layer are hot melt bonded to the membrane electrode assembly (MEA) 20. The thickness retention rate of the hot melt adhesive layer was evaluated according to the following criteria. standard Excellent: The thickness (center part) of the hot melt adhesive layer after bonding is 80% or more of the thickness (center part) of the hot melt adhesive layer before bonding. Unacceptable: The thickness (center part) of the hot melt adhesive layer after bonding is less than 80% of the thickness (center part) of the hot melt adhesive layer before bonding. The results of investigating the thickness retention rate of the hot melt adhesive layer are shown in Table 3 below.
[0166] (embedding by hot melt adhesive layer) The PEN films with hot melt adhesive layers according to each Example and the PEN films with hot melt adhesive layers according to each Comparative Example were examined for embedding ability by the hot melt adhesive layer after being adhered to the solid electrolyte membrane of a polymer electrolyte fuel cell. The embeddability of the hot melt adhesive layer was evaluated by adhering two sheets of each PEN film with a hot melt adhesive layer of each Example and Comparative Example to a membrane / electrode assembly (MEA) 20 according to the above procedure, and then observing the adhesion state of the two PEN films with a hot melt adhesive layer using a laser microscope. The observation magnification of the laser microscope was 400 times. The embedding property of the hot melt adhesive layer was evaluated according to the following criteria. standard Excellent: The distance from the outer edge of the solid electrolyte membrane to the hot melt adhesive layer is 200 μm or less. Not acceptable: The distance between the outer edge of the solid electrolyte membrane and the hot melt adhesive layer exceeds 200 μm. The results of investigating the embedding ability of the hot melt adhesive layer are shown in Table 3 below.
[0167] [Table 3]
[0168] From Table 3, it can be seen that in the PEN films with the hot melt adhesive layer according to each Example, both the thickness retention rate and embeddability were rated as "excellent." In contrast, it can be seen that the PEN films with hot melt adhesive layers according to the respective comparative examples were rated as "unacceptable" in terms of both thickness retention and embeddability.
[0169] Next, compositions for hot melt adhesive layers according to Test Examples 1 to 20 were prepared as described below.
[0170] [Test Example 1] With the same formulation as in Example 10, a composition for a hot melt adhesive layer according to Test Example 1 was obtained.
[0171] [Test Example 2] A composition for a hot melt adhesive layer according to Test Example 2 was obtained in the same manner as in Test Example 1, except that the amount of epoxy resin B1 was changed from 25 parts by mass to 30 parts by mass.
[0172] [Test Example 3] A composition for a hot melt adhesive layer according to Test Example 3 was obtained in the same manner as in Test Example 1, except that the amount of epoxy resin B1 was changed from 25 parts by mass to 35 parts by mass.
[0173] [Test Example 4] With the same formulation as in Example 11, a composition for a hot melt adhesive layer according to Test Example 4 was obtained.
[0174] [Test Example 5] A composition for a hot melt adhesive layer according to Test Example 5 was obtained in the same manner as in Test Example 4, except that the amount of the epoxy resin B2 was changed from 25 parts by mass to 30 parts by mass.
[0175] [Test Example 6] A composition for a hot melt adhesive layer according to Test Example 6 was obtained in the same manner as in Test Example 4, except that the amount of the epoxy resin B2 was changed from 25 parts by mass to 35 parts by mass.
[0176] [Test Example 7] A composition for a hot melt adhesive layer according to Test Example 7 was obtained in the same manner as in Comparative Example 10, except that the amount of epoxy resin B1 was changed from 25 parts by mass to 20 parts by mass.
[0177] [Test Example 8] A composition for a hot melt adhesive layer according to Test Example 8 was obtained in the same manner as in Comparative Example 11, except that the amount of the epoxy resin B2 was changed from 25 parts by mass to 20 parts by mass.
[0178] [Test Example 9] With the same formulation as in Comparative Example 10, a composition for a hot melt adhesive layer according to Test Example 9 was obtained.
[0179] [Test Example 10] With the same formulation as in Comparative Example 11, a composition for a hot melt adhesive layer according to Test Example 10 was obtained.
[0180] [Test Example 11] A composition for a hot melt adhesive layer according to Test Example 11 was obtained in the same formulation as in Test Example 1, except that the epoxy resin B1 was not added.
[0181] [Test Example 12] With the same formulation as in Comparative Example 12, a composition for a hot melt adhesive layer according to Test Example 12 was obtained.
[0182] [Test Example 13] A composition for hot melt adhesive layer relating to Test Example 13 was obtained with the same formulation as Test Example 1, except that a sixth crystalline polyester resin (manufactured by TOYOBO Corporation under the trade name "GM-350") was used instead of the second crystalline polyester resin.
[0183] [Test Example 14] A composition for a hot melt adhesive layer according to Test Example 14 was obtained in the same formulation as in Test Example 4, except that the sixth crystalline polyester resin was used instead of the second crystalline polyester resin.
[0184] [Test Example 15] A composition for hot melt adhesive layer relating to Test Example 15 was obtained with the same formulation as Test Example 1, except that the seventh crystalline polyester resin (manufactured by TOYOBO Corporation under the trade name "GM-900") was used instead of the second crystalline polyester resin.
[0185] [Test Example 16] A composition for a hot melt adhesive layer according to Test Example 16 was obtained in the same formulation as in Test Example 4, except that the seventh crystalline polyester resin was used instead of the second crystalline polyester resin.
[0186] [Test Example 17] A composition for hot melt adhesive layer according to Test Example 17 was obtained using the same formulation as in Test Example 1, except that the amount of isocyanate-based crosslinking agent (C) (Takenate D-110N) was changed from 10 parts by mass to 15 parts by mass.
[0187] [Test Example 18] A composition for hot melt adhesive layer according to Test Example 18 was obtained using the same formulation as in Test Example 4, except that the amount of isocyanate-based crosslinking agent (C) (Takenate D-110N) was changed from 10 parts by mass to 15 parts by mass.
[0188] [Test Example 19] A composition for hot melt adhesive layer according to Test Example 19 was obtained using the same formulation as in Test Example 1, except that the amount of isocyanate-based crosslinking agent (C) (Takenate D-110N) was changed from 10 parts by mass to 5 parts by mass.
[0189] [Test Example 20] A composition for hot melt adhesive layer according to Test Example 20 was obtained using the same formulation as in Test Example 4, except that the amount of isocyanate-based crosslinking agent (C) (Takenate D-110N) was changed from 10 parts by mass to 5 parts by mass.
[0190] The formulations of the compositions for hot melt adhesive layers according to Test Examples 1 to 20 are shown in Table 4 below.
[0191] [Table 4]
[0192] In addition, various physical properties of the sixth crystalline polyester resin (GM-350) and the seventh crystalline polyester resin (GM-900) are shown in Table 5 below.
[0193] [Table 5]
[0194] [Coating of the composition for hot melt adhesive layer] The PEN films with hot melt adhesive layers of each test example were obtained in the same manner as in the case of the PEN films with hot melt adhesive layers of each example and each comparative example, except that the composition for the hot melt adhesive layer of each test example was used.
[0195] [Preparation of first adhesive sheet] Two PEN films with hot melt adhesive layers of each test example were prepared, and the two PEN films with hot melt adhesive layers were overlapped so that the hot melt adhesive layers were in contact with each other. Using a laminator adjusted to 140° C., two PEN films with hot melt adhesive layers of each test example were bonded together by thermocompression bonding to prepare a first adhesive sheet for each test example.
[0196] [Preparation of the second adhesive sheet] The PEN film with the hot melt adhesive layer of each test example was superimposed on a perfluorocarbon sulfonic acid resin sheet so that the exposed surface of the hot melt adhesive layer of the PEN film with the hot melt adhesive layer of each test example was in contact with one side of the perfluorocarbon sulfonic acid resin sheet (tetrafluoroethylene / perfluoro[2-(fluorosulfonylethoxy)propyl vinyl ether] copolymer membrane (manufactured by DuPont, product name "NAFIONN-115")) (having the same shape as the film with the hot melt adhesive layer). Using a laminator adjusted to 140°C, the PEN film with the hot melt adhesive layer of each test example and a perfluorocarbon sulfonic acid resin sheet were bonded together by thermal compression to produce a second adhesive sheet for each test example.
[0197] [Hot water resistance 1] For the first adhesive sheet of each test example, a test specimen measuring 10 mm wide x 80 mm long was cut out from the first adhesive sheet of each test example, and the test specimen was immersed in hot water at 95°C for 1,000 hours. After cooling to room temperature, the hot water resistance of each test specimen was evaluated according to the following criteria. Excellent: No peeling observed after immersion. · Unacceptable: Peeling is observed after immersion.
[0198] [Acid resistance 1] For the first adhesive sheet of each test example, a test specimen measuring 10 mm wide x 80 mm long was cut out from the first adhesive sheet of each test example, and the test specimen was immersed in dilute sulfuric acid of pH 2 at 95°C for 1,000 hours. After cooling to room temperature, the acid resistance of each test specimen was evaluated according to the following criteria. Excellent: No peeling observed after immersion. · Unacceptable: Peeling is observed after immersion.
[0199] [Alcohol resistance 1] For the first adhesive sheet of each test example, a test specimen measuring 10 mm wide x 80 mm long was cut out from the first adhesive sheet of each test example, and the test specimen was immersed in a 95°C water-ethylene glycol mixed solution (ethylene glycol mixing ratio: 50% by volume) for 1,000 hours. After cooling to room temperature, the alcohol resistance of each test specimen was evaluated according to the following criteria. Excellent: No peeling observed after immersion. · Unacceptable: Peeling is observed after immersion.
[0200] [Hot water resistance 2] For the second adhesive sheet of each test example, a test specimen measuring 10 mm wide x 80 mm long was cut out from the second adhesive sheet of each test example, and the test specimen was immersed in hot water at 95°C for 1,000 hours. After cooling to room temperature, the hot water resistance of each test specimen was evaluated according to the following criteria. Excellent: No peeling observed after immersion. · Unacceptable: Peeling is observed after immersion.
[0201] [Acid resistance 2] For the second adhesive sheet of each test example, a test specimen measuring 10 mm wide x 80 mm long was cut out from the second adhesive sheet of each test example, and the test specimen was immersed in dilute sulfuric acid of pH 2 at 95°C for 1,000 hours. After cooling to room temperature, the acid resistance of each test specimen was evaluated according to the following criteria. Excellent: No peeling observed after immersion. · Unacceptable: Peeling is observed after immersion.
[0202] [Alcohol resistance 2] For the second adhesive sheet of each test example, a test specimen measuring 10 mm wide x 80 mm long was cut out from the second adhesive sheet of each test example, and the test specimen was immersed in a 95°C water-ethylene glycol mixed solution (ethylene glycol mixing ratio: 50% by volume) for 1,000 hours. After cooling to room temperature, the alcohol resistance of each test specimen was evaluated according to the following criteria. Excellent: No peeling observed after immersion. · Unacceptable: Peeling is observed after immersion.
[0203] The results of evaluating the hot water resistance 1, acid resistance 1, and alcohol resistance 1 for the first adhesive sheet of each test example are shown in Table 5 below, and the results of evaluating the hot water resistance 2, acid resistance 2, and alcohol resistance 2 for the second adhesive sheet of each test example are shown in Table 6 below.
[0204] [Table 6]
[0205] It can be seen from Table 6 above that in Test Examples 1 to 6, for both the first adhesive sheet and the second adhesive sheet, all evaluation items were rated "excellent," meaning that no peeling was observed. In contrast, in Test Examples 7 to 20, all evaluation items for both the first adhesive sheet and the second adhesive sheet were rated as "fail," meaning that peeling was observed. [Explanation of symbols]
[0206] 10 hot melt adhesive sheet, 20 membrane / electrode assembly (MEA), 201 solid electrolyte membrane, 202 positive electrode, 203 negative electrode, 10a substrate, 10b adhesive layer, 201a positive electrode side electrolyte membrane exposed region, 201b negative electrode side electrolyte membrane exposed region, 202a positive electrode catalyst layer, 202b positive electrode gas diffusion layer, 203a negative electrode catalyst layer, 203b negative electrode gas diffusion layer, 202a1 positive electrode side catalyst layer exposed region, 203a1 negative electrode side catalyst layer exposed region, L1 1st boundary line, L2 2nd boundary line, L3 3rd boundary line, L4 4th boundary line.
Claims
1. A hot melt adhesive sheet having an adhesive layer formed of a hot melt adhesive laminated on at least one surface of a substrate, The hot melt adhesive includes a crosslinked product of an adhesive composition including a crosslinking agent, the adhesive composition including a polyester resin, an epoxy resin, and an isocyanate-based crosslinking agent; The epoxy resin includes a bisphenol type epoxy resin and a rubber-modified epoxy resin, The bisphenol type epoxy resin has an epoxy equivalent of 450 g / eq or more and 1000 g / eq or less. Hot melt adhesive sheet.
2. The polyester resin includes a crystalline polyester resin having a softening point of 120° C. or higher. The hot melt adhesive sheet according to claim 1 .
3. The bisphenol type epoxy resin includes a bisphenol A type epoxy resin. The hot melt adhesive sheet according to claim 1 or 2.
4. The rubber-modified epoxy resin is an NBR-modified epoxy resin. The hot melt adhesive sheet according to claim 1 or 2.
5. Used by adhering to the solid electrolyte membrane of polymer electrolyte fuel cells The hot melt adhesive sheet according to claim 1 or 2.
Citation Information
Patent Citations
Epoxy resin modified anticorrosive polyester hot melt adhesive and preparation method thereof
CN117551411A
Method of bonding with photoreactive hot-melt adhesive
JP2002317169A
Seal material and hot-melt adhesive
JP2015168724A
Hot-melt adhesive sheet
JP2023151005A
Hot melt adhesive sheet
JP2023174368A